A CASE STUDY ANALYSIS OF SUSTAINABLE MANUFACTURING PRACTICE IN MALAYSIAN MANUFACTURING FIRM (Journal of Technology and Operations Management, 2018)
The aim of the present study is to explore the implementation of sustainable manufacturing practice in Malaysian manufacturing firms. In specific, there are three research questions that guide the study such as: (i) which type of sustainable manufacturing practice is being implemented by the studied firms?; (ii) why do the studied firms tend to implement sustainable manufacturing practice in their operations?; and (iii) what are the impacts of implementing sustainable manufacturing practice on the firms. An electrical and electronic firm located in Penang was chosen as the study sample, and the data was collected from the firm by using semi-structured questions. A manager who had both technical and management knowledge and experience in operational and business activities in the chosen firm was interviewed. The interview was recorded, transcribed, and analysed based on the research questions. The findings of the present study discover the various types of sustainable manufacturing practices being implemented by the firm, two drivers (i.e. internal and external drivers) that motivate the firm to implement sustainable manufacturing practice, and the impacts of sustainable manufacturing implementation in the aspect of economic, environmental, and social sustainability of the firm. The present study is very useful as it offers some theoretical and practical contributions.